RELIGIOUS ORIENTATION AND SOCIAL INTERACTION IN RELIGIOUS MINORITY COMMUNITIES TO SUPPORT RELIGIOUS - Sukarti; I Made Wiradiana; I Nyoman Alit Putrawan (UHN I Gusti Bagus Sugriwa Denpasar, 2024)
The application of religious values can support the creation of harmony in social interactions insociety. Religious diversity can be a beautiful pluralistic description, but it can also hurt the socialinteraction of religious people if each religious group tends to prioritize its egocentricity. Thisstudy aims to analyze religious orientation and social interaction in minority religious communitiesto maintain religious identity. This study uses a descriptive qualitative method with a literaturestudy approach. The results of the study found that religious orientation in minority religiouscommunities in Indonesia tends to be close to religiosity. There is a dialectical tension betweenhumans (as individuals) who intersect with the overall life in society and the construction of belief(faith). For minority groups, religion is always used as a guide or way of life. The noble values ofreligion with high tolerance become a benchmark in the process of interaction with a pluralisticsociety. Efforts to maintain religious identity in minority religious groups are carried out throughcultural and religious syncretism which is the social environment and reference group.